Implementation of security system for bank using open CV and RFID - Neeraja, Kona; Rama Chandra Rao, Potu; Suman Maloji, Dr; Mohammed Ali Hussain, Dr (International Journal of Engineering and Technology, 2018)
Security is one of the major concerns in banking sector where we can adapt the latest techniques like face recognition and RFID we can provide better security policies. In this paper we have proposed a model with two major security techniques. The First method provides security for the locker room door by face recognition using OpenCV. Face recognition is a particular type of biometric system that can be used to analyze the obtained information and identify the user uniquely by the trained images. In this proposed model the images of customers are trained. A Microsoft Lifecam HD-3000 is placed outside the locker room. This camera detects the human face using Haar Cascade Classifier and recognizes a customer using LBPH Algorithm. If a trained customer tries to enter then door is unlocked. The customer name is uploaded to cloud. The second method provides security to the cashier cabin by using MFRC522 RFID Module which is very easy to access which consumes less time and more secured compared to the existing system. When an authorized tag is recognized the door is unlocked for certain time period and the userid is uploaded to the cloud. By using these two techniques we can provide security for locker room and cashier cabins in any banking sector.